ANALISIS DAMPAK FATWA MUI NO 83 TAHUN 2023 TERHADAP MINAT BELI KONSUMEN STUDI PADA ASN DI PEMERINTAHAN PROVINSI LAMPUNG - Nurhaliza, Siti; Albab, Ulil; Sutopo, Heri (Bisnis-Net, 2024)
Fatwa of the Indonesian Ulema Council (MUI) Number 83 of 2023 which states that defending Israeli aggression against Palestine is haram, triggered a significant reaction among Indonesian society, especially ASN within the Lampung Provincial Government. This research aims to examine the impact of MUI Fatwa Number 83 of 2023 concerning Interest in Purchasing ASN (State Civil Apparatus) within the Lampung Provincial Government on products from companies involved in illegal activities in Palestine. This research applies qualitative methods through in-depth interview techniques to obtain data from ASN who work in the Lampung Provincial Government Office and its surroundings as respondents. The research results show a significant change in ASN buying interest, where the majority of respondents began to avoid products affiliated with companies involved in illegal activities and looked for alternatives that were in accordance with their religious principles. This change has an impact on reducing ASN's buying interest in affiliated products, as well as fulfilling ASN's compliance with the Fatwa issued by the MUI. However, some respondents still have difficulty finding alternative products that are equivalent in terms of quality and price, so this research highlights that a full transition to alternative products may require more time and effort.